A Proteome Translocation Response to Complex Desert Stress Environments in Perennial Phragmites Sympatric Ecotypes with Contrasting Water Availability - Li, Li; Chen, Xiaodan; Shi, Lu; Wang, Chuanjing; Fu, Bing; Qiu, Tianhang; Cui, Suxia (Frontiers in Plant Science, 2017)
After a long-term adaptation to desert environment, the perennial aquatic plant Phragmites communis has evolved a desert-dune ecotype. The desert-dune ecotype (DR) of Phragmites communis showed significant differences in water activity and protein distribution compared to its sympatric swamp ecotype (SR). Many proteins that were located in the soluble fraction of SR translocated to the insoluble fraction of DR, suggesting that membrane-associated proteins were greatly reinforced in DR. The unknown phenomenon in plant stress physiology was defined as a proteome translocation response. Quantitative 2D-DIGE technology highlighted these ‘bound’ proteins in DR. Fifty-eight kinds of proteins were identified as candidates of the translocated proteome in Phragmites. The majority were chloroplast proteins. Unexpectedly, Rubisco was the most abundant protein sequestered by DR. Rubisco activase, various chaperons and 2-cysteine peroxiredoxin were major components in the translocation response. Conformational change was assumed to be the main reason for the Rubisco translocation due to no primary sequence difference between DR and SR. The addition of reductant in extraction process partially reversed the translocation response, implying that intracellular redox status plays a role in the translocation response of the proteome. The finding emphasizes the realistic significance of the membrane-association of biomolecule for plant long-term adaptation to complex stress conditions.